Enhanced anticancer effect of lysozyme-functionalized metformin-loaded shellac nanoparticles on a 3D cell model: role of the nanoparticle and payload concentrations - Wang, Anheng; Madden, Leigh A; Paunov, Vesselin N (Biomaterials science, 2024)
Here we used a 3D human hepatic tumour cell culture model to assess the in vitro efficacy of "active" metformin-loaded nanoparticles (NPs) as anticancer therapeutics. The metformin nanocarrier design was repurposed from previous studies targeting bacterial and fungal biofilms with antimicrobials loaded in protease-coated nanoparticles. These active nanocarriers were constructed with shellac cores loaded with metformin as the anticancer agent and featured a surface coating of the cationic protease lysozyme. The lysozyme's role as a nanocarrier surface coating is to partially digest the extracellular matrix (ECM) of the 3D tumour cell culture which increases its porosity and the nanocarrier penetration. Hep-G2 hepatic 3D clusteroids were formed using a water-in-water (w/w) Pickering emulsion based on an aqueous two-phase system (ATPS). Our specific metformin nano-formulation, comprising 0.25 wt% lysozyme-coated, 0.4 wt% metformin-loaded, 0.2 wt% shellac NPs sterically stabilized with 0.25 wt% Poloxamer 407, demonstrated significantly enhanced anticancer efficiency on 3D hepatic tumour cell clusteroids. We examined the role of the lysozyme surface functionality of the metformin nanocarriers in their ability to kill both 2D and 3D hepatic tumour cell cultures. The anticancer efficiency at high metformin payloads was compared with that at a high concentration of nanocarriers with a lower metformin payload. It was discovered that the high metformin payload NPs were more efficient than the lower metformin payload NPs with a higher nanocarrier concentration. This study introduces a reliable in vitro model for potential targeting of solid tumours with smart nano-therapeutics, presenting a viable alternative to animal testing for evaluating anticancer nanotechnologies. We report a novel approach for effective targeting of 3D tumour cell culture based on protease-functionalised metformin nanocarriers and explore the roles of the nanoparticle concentration and the drug payload.